Mirrors and toothaches: commonplace manipulations of non-auditory feedback availability change perceived speech intelligibility - Casserly, Elizabeth D.; Marino, Francesca R. (Frontiers in Human Neuroscience, 2024)
This paper investigates the impact of two non-technical speech feedback perturbations outside the auditory modality: topical application of commercially-available benzocaine to reduce somatosensory feedback from speakers’ lips and tongue tip, and the presence of a mirror to provide fully-detailed visual self-feedback. In experiment 1, speakers were recorded under normal quiet conditions (i.e., baseline), then again with benzocaine application plus auditory degradation, and finally with the addition of mirror feedback. Speech produced under normal and both feedback-altered conditions was assessed via naïve listeners’ intelligibility discrimination judgments. Listeners judged speech produced under bisensory degradation to be less intelligible than speech from the un-degraded baseline, and with a greater degree of difference than previously observed with auditory-only degradation. The introduction of mirror feedback, however, did not result in relative improvements in intelligibility. Experiment 2, therefore, assessed the effect of a mirror on speech intelligibility in isolation with no other sensory feedback manipulations. Speech was recorded at baseline and then again in front of a mirror, and relative intelligibility was discriminated by naïve listeners. Speech produced with mirror feedback was judged as less intelligible than baseline tokens, indicating a negative impact of visual self-feedback in the absence of other sensory manipulations. The results of both experiments demonstrate that relatively accessible manipulations of non-auditory sensory feedback can produce speech-relevant effects, and that those effects are perceptible to naïve listeners.